Anomalies detection in adhesive wall tiling systems by infrared thermography - Lourenço, Tomás Caldeira (2017)
Tiling systems for building facade coatings are widely used all over the world. Despite very common, mainly due to its aesthetic characteristics, this kind of cladding is characterised by a complex application, given the fact that it is a system in direct contact with a support (the rendered wall) and composed by three different components with specific characteristics and technical requirements: the tiles, the adhesive grout, and the joint grout. This complexity can result in several possible anomalies, as it is the case of detachment, the most common onerous one and probably the most difficult anomaly to early diagnosis in this type of cladding. Infrared thermography is a non-destructive testing method with a broad applicability in buildings’ inspection. The method consists in using a thermal camera that, by detecting thermal radiation, reads thermal variations that can indicate the presence of anomalies. Taking into account this diagnosis method’s potential, it was developed in LNEC a wide study where the results of thermographic surveys on laboratory specimens, exterior panels cladded with tiles with controlled anomalies and case studies of real situations are presented. In order to characterize the claddings behaviour and the anomalies’ detectability using this method, in a first phase eight specimens were studied in laboratory with differences in terms of: colour, thickness, kind of support, finishing and presence of anomaly. In a second phase, four panels divided into two experimental cells, located in LNEC’s campus, aiming to evaluate the diagnostic technique in exterior facades with differences in terms of tiles’ colour and support of application. As a complement of the laboratory surveys (indoors and outdoors) certain features of this kind of cladding were characterized, such as their emittance and reflectance. In order to evaluate infrared thermography’s diagnosis capability in real and unfamiliar situations, two real cases of buildings in Lisbon, cladded with ceramic tiles, were studied. The results obtained in the form of thermal differentials between “normal” and “anomalous” zones in a tiled facade or specimen proved that Infrared Thermography can be a valuable tool to early identification of anomalies, mainly detachments, in this kind of coating systems.